The clinical effectiveness and cost-effectiveness of enzyme replacement therapy for Gaucher's disease: a systematic review - Connock, M; Burls, A; Frew, E; Fry-Smith, A; Juarez-Garcia, A; McCabe, C; Wailoo, A; Abrams, K; Cooper, N; Sutton, A; O'Hagan, A; Moore, D (2006)
The aim of this review is to determine the clinical effectiveness and cost-effectiveness of enzyme replacement therapy (ERT) in the treatment of symptomatic Gaucher's disease. Major electronic databases were searched from their inception to August 2003; and updated from January 2003 to July/August 2004. Databases were searched for studies that met the criteria and selected data were extracted and evaluated. Studies were assessed for their relevance to the UK context and the revie cost-effectiveness ratio (ICER)] in the base case ranged from pounds sterling 380,000 to pounds sterling 476,000 per QALY, depending on genotype. Univariate sensitivity analyses examined ERT not restoring full health, more severe disease progression in the untreated cohort, and only treating the most severely affected patients. These produced ICERs of approximately pounds sterling 1.4 million, pounds sterling 296,000 and pounds sterling 275,000 per QALY, respectively. The base-case unit cost of the drug is pounds sterling 2.975. The unit cost would have had to be reduced ten-fold, to pounds sterling 0.30, to obtain an ICER of pounds sterling 30,000 per QALY. At a unit cost of pounds sterling 1 the ICER would be pounds sterling 120,000 per QALY. Although ERT for treating the 'average' Gaucher's disease patient exceeds the normal upper threshold for cost-effectiveness seen in NHS policy decisions by over ten-fold, some argue that since orphan drug legislation encouraged the manufacture of Cerezyme, and Gaucher's disease can be defined as an orphan disease, the NHS has little option but to provide it, despite its great expense. More information is required before the generalisability of the findings can be determined. Although data from the UK have been used wherever possible, these were very thin indeed. Nonetheless, even large errors in estimates of the distribution of genotype, genotype--phenotype associations, effectiveness and numbers of patients will not reduce the ICER to anywhere near the upper level of treatments usually considered cost-effective. Further research could help to clarify the many uncertainties that exist. However, although doing so will be of clinical interest, it is questionable whether, within the current pricing environment, such research would have any substantive impact on policy decisions. It is highly improbable that, whatever the findings of such research, the ICER could be brought down by the orders of magnitude required to make ERT an efficient use of health service resources. (The possible exception to this would be investigating the most efficient alternative treatment strategies for using ERT in a paediatric population only.) Moreover, if under equity considerations for orphan diseases the NHS feels it is important to provide this drug, regardless of its cost-effectiveness, then refining the precision of the ICER estimate also becomes superfluous.